Illusion of consent : engaging with Carole Pateman - O'Neill, Daniel I., 1967-; Shanley, Mary Lyndon, 1944-; Young, Iris Marion, 1949-2006 (Pennsylvania State University Press, 2008)
"A collection of essays that discuss the writings of Carole Pateman, with emphasis on her theories of democracy and feminism"--Provided by publisher